Estimation of methane generation in three Philippine landfills - Theingi Soe
Mitigation of fugitive methane emission from landfill has been a great concern all over the world. In performing landfill methane mitigation program, estimation of methane generation is important and can be done by using LandGEM model developed by the US EPA. The key parameters used in LandGEM: methane generation potential (Lo) and decay rate (k) are parameters which need to be determined using site specific data. This study estimated Lo and k for three case study landfills (P, Q, and R Landfills) located in the different regions in the Philippines using DOC content, first order kinetic equation and fitting analysis of model outcome to actual collected gas data on the basis of available waste data and gas data. Applying different MCF factor based on different landfill conditions, L0 obtained were 43, 56 and 33 m3/Mg for P, Q and R Landfills, respectively. k obtained for P Landfill were 0.01 y-1 for kinetic equation and 0.24 y-1 for fitting analysis. k values estimated by first order kinetic equation for Q Landfill were 0.16 y-1 for base layer and 0.17 y-1 for middle layer, and for R Landfill was 0.07 y-1. Using calculated model parameters, this study also investigated the potential of recoverable energy from case studied landfills for 20-year landfill gas to energy project (LFGTE). Applying 45% gas collection efficiency to P and R Landfills, cumulative collectible methane and its equivalent amount of C02 reduction are 32,298 Mg and 672,521 t of C02 for P Landfill and 890 Mg and 18,689 t of C02 for R Landfill. 67% of collection efficiency was applied to Q Landfill and its collectible methane is 8,242 Mg which is equivalent to 173,080 t of C02 reduction. The scenario of diversion of compostable waste (food and garden) was applied to Q Landfill. It can be concluded that for the landfills where compostable waste diversion is not practiced, gas collection system for LFGTE project should be started in the beginning of receiving waste to maximize benefits from electricity generation.